Directional transition from initiation to elongation in bacterial translation - Goyal, Akanksha (2015)
The transition of the 30S initiation complex (IC) to the translating 70S ribosome after 50S subunit joining provides an important checkpoint for mRNA selection during translation in bacteria. Here, we study the timing and control of reactions that occur during 70S IC formation by rapid kinetic techniques, using a toolbox of fluorescence-labeled translation components. We present a kinetic model based on global fitting of time courses obtained with eight different reporters at increasing concentrations of 50S subunits. IF1 and IF3 together affect the kinetics of subunit joining, but do not alter the elemental rates of subsequent steps of 70S IC maturation. After 50S subunit joining, IF2-dependent reactions take place independent of the presence of IF1 or IF3. GTP hydrolysis triggers the efficient dissociation of fMet-tRNAfMet from IF2 and promotes the dissociation of IF2 and IF1 from the 70S IC, but does not affect IF3. The presence of non-hydrolyzable GTP analogs shifts the equilibrium towards a stable 70S–mRNA–IF1–IF2–fMet-tRNAfMet complex. Our kinetic analysis reveals the molecular choreography of the late stages in translation initiation.